Klövvilt- och fordonskollisioner - Riikonen, Marielle (2016)
The expansion of the road network and the rise of traffic volume, as well as the growth in the population size of many ungulate species leads to an increase of ungulate-related accidents. Ungulate-vehicle collisions are a major road safety issue which causes considerable mortality among many species. It also leads to huge animal suffering and reduce the animal welfare. If several ungulate-vehicle collisions occur at the same site they will create a cluster of ungulate accidents. Those places represent high risk areas for human and animal safety. The aim of this study was to analyze the stability of clusters of ungulate accidents with moose, roe deer, fallow deer, red deer and wild boar from 2010 to 2015 to investigate if the clusters that have been stable and the stability of those clusters differ between the species. Stable means that the number of accidents has changed very little during the six years. Further, the purpose of this study was also to investigate whether the differences in ungulate social organization may contribute to the stability of the clusters. To accomplish the purpose of this study, 11 746 clusters of ungulate accidents were analyzed. The results showed that all the species has different percentage of the clusters that have been stable. Deer has the highest percentage (25 %), thereafter roe deer (24 %), wildboar (12 %) and moose, which has the lowest (6 %). In these stable clusters the stability differs with statistical significance between all the species, except between roe deer and wild boar. From the results it is clear that the stability has been considerably higher in the clusters consisting of fallow deer and red deer, than in those who concern the remaining species. Clusters consisting of roe deer and wild boar accidents have the second highest stability, while the moose have the lowest. The fallow deer and red deer are living in large social groups, the wild boars in family groups while moose and roe deer live solitary. This implies that the socially living animals are more concentrated to a few places than the solitary species. Judging from the results, the social organization contributes a difference in stability between the studied species. The result of this study can be applied to reduce ungulate-vehicle collisions at the locations where the accidents has occurred regularly and where they are likely to occur again. Because the ungulate population increases the results may also be applied to effectively implement preventive measures to locations where the species will spread. If these parameters are taken into account, the ungulate-vehicle collisions can be prevented in a faster phase and the animal suffering can be reduced.